2020
DOI: 10.1007/s00300-020-02655-w
|View full text |Cite
|
Sign up to set email alerts
|

Degree of herbivory and intestinal morphology in nine notothenioid fishes from the western Antarctic Peninsula

Abstract: Although many notothenioid fishes are primarily carnivorous, some species consistently feed on macroalgae and are therefore omnivorous. Among fish, the degree of herbivory is usually reflected in the morphology of the gastrointestinal system especially intestine length. We examined a large number of juvenile and adult specimens of nine sympatric notothenioid species collected sequentially over eight summer seasons at Potter Cove, South Shetland Islands. We provide relative intestine lengths (RIL), distinct pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…There were small differences between the epithelial cells in the pyloric caeca and anterior GIT of the present study species, but their generally similar structures imply that these two regions have a similar function. The large variation in number of pyloric caeca among study species suggests that the number does not relate to function or specific diet type, consistent with studies on other groups of fishes (e.g., Moreira et al, 2020).…”
Section: Morphology Of the Gastrointestinal Tractsupporting
confidence: 85%
“…There were small differences between the epithelial cells in the pyloric caeca and anterior GIT of the present study species, but their generally similar structures imply that these two regions have a similar function. The large variation in number of pyloric caeca among study species suggests that the number does not relate to function or specific diet type, consistent with studies on other groups of fishes (e.g., Moreira et al, 2020).…”
Section: Morphology Of the Gastrointestinal Tractsupporting
confidence: 85%
“…Their number is a species-specific trait, varying from a few appendages in fish such as spotted snakehead ( Channa punctata ) to several hundred in Atlantic cod ( Gadus morhua ) [ 26 ]. They are absent in stomachless fish [ 43 , 47 , 48 ]. Previous studies have not shown a correlation between the number of pyloric caeca and the type of food [ 26 ]; however, their numbers are lower in omnivorous and herbivorous species than in carnivorous species [ 49 ] due to the need to digest chemically and structurally more demanding foods.…”
Section: Discussionmentioning
confidence: 99%
“…The heads of some «cryonotothenioids» display specialized morphology for the acquisition of prey, but the alimentary canal from the esophagus to the rectum is generally similar in its gross morphology and histology in the species studied to date. The interspecific differences include: (1) a phylogenetic decrease in mean number of pyloric caeca from 6-7 in most nototheniids to 2 in channichthyids, although Dacodraco has 4; (2) a maximum ≈1.5-fold difference in average relative stomach lengths; and (3) a maximum ≈2-fold difference in average relative intestine lengths (Ojeda, 1986; Eastman and DeVries, 1997; Eastman 1999; Moreira et al, 2020) [195][196][197][198]. The absence of specialization may be attributable to the opportunistic feeding and dietary plasticity of many species.…”
Section: Morphology Stage-axis 6: Trophic Morphology Specifically Ora...mentioning
confidence: 99%
“…For example, depending on the time of year and location, the alimentary canal of Notothenia coriiceps processes food on a scale ranging from carnivory to omnivory to herbivory (Barrera-Oro and Casaux et al, 1990) [69,153], although perhaps less efficiently that if it was more specialized for only carnivory or herbivory. Hence there is no morphology that reflects intermittent herbivory on kelp, and attempts to correlate diet with stomach length, intestine length, or number of pyloric caeca are inconclusive (Moreira et al, 2020) [198]. There may also be non-dietary influences on gut morphology.…”
Section: Morphology Stage-axis 6: Trophic Morphology Specifically Ora...mentioning
confidence: 99%
See 1 more Smart Citation